Conceptual design of steam engine for motorcar: steam generator development / Mohamed Al Hafiz Zamanhuri - Zamanhuri, Mohamed Al Hafiz (2009)
This project presents the conceptual design of steam generator development to install in the conceptual steam car engine. Because of the usage of petrol in internal combustion engine can be considered as impractical when the petrol price is not stable in today's market, so that, the development on conceptual design of steam car engine are done to overcome this problem. Focus more on conceptual design of steam engine as steam generating system and then the steam are supply to engine for power generation to move the car. The steam generating system is developing to meet the requirement that need by the engine to produce the power. Design concepts were done by using the CATIA V5R14 software. Basically, had two types of steam generator which is water tube and fire tube steam generator. Fire tubes are more suitable to install in steam car because it many use in locomotive system also it size smaller than the water tube steam generator. So that this conceptual design will help to overcome the fuel problem and can create more efficient system that we can install in future car.